Answer:
The y = m x + b form of the given equation is y = x + 3
Explanation:
Here, the given equation is :
2 y - 2 x = 6
Now, to convert it in the form y = m x + b
Consider the given expression:
![2 y - 2 x = 6 \implies 2 y = 6 + 2 x\\\implies y = \frac {6+2x}{2} = (6)/(2) + (2x)/(2) \\\implies y = 3 + x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8qe0a75d1y7gwe22t4cpos92hokqw2x7il.png)
Therefore, here the y = m x + b form of the given equation is y = x + 3
Here. slope m = 1,and Y - intercept b = 3